Acamprosate Modulates Alcohol-Induced Hippocampal NMDA Receptors and Brain Microsomal Ca2+-ATPase but Induces Oxidative Stress in Rat - Caliskan, Ali Metehan; Naziroglu, Mustafa; Uguz, Abdulhadi Cihangir; Ovey, Ishak Suat; Sutcu, Recep; Bal, Ramazan; Ozcankaya, Ramazan (Springer, 2010)
We investigated the effects of acamprosate on alcohol-induced oxidative toxicity, microsomal membrane Ca2+-ATPase (MMCA) activity and N-methyl-D-aspartate receptor (NMDAR) subunits in rat brain. Forty male rats were equally divided into four groups. The first group was used as control, and the second group received ethanol. Acamprosate and acamprosate plus ethanol each day were administered to rats constituting the third and fourth groups for 21 days, respectively. Brain cortical and hippocampal samples were taken from the four groups after 21 days. Brain cortical lipid peroxidation (LP) levels and MMCA activity were higher in the alcohol group than in control, although glutathione peroxidase (GSH-Px), vitamin C, vitamin E and beta-carotene values were lower in the alcohol group than in control. LP levels were further increased in the acamprosate and alcohol + acamprosate groups compared with the alcohol group. GSH-Px, vitamin A, vitamin C, vitamin E and beta-carotene in the acamprosate and alcohol + acamprosate groups were further decreased compared with the alcohol group. Hippocampal NMDAR 2A and 2B subunit concentrations were lower in the alcohol group than in control, although they were increased by acamprosate and alcohol + acamprosate. Brain cortical MMCA activity was higher in the acamprosate group than in the alcohol-treated rats, although its activity was lower in the alcohol + acamprosate group than in the acamprosate group. Brain cortical reduced glutathione levels were not found to be statistically different in any of the groups. Oxidative stress has been proposed to explain the biological side effects of experimental alcohol intake. Acamprosate and alcohol-induced oxidative stress decreased brain antioxidant vitamins in the alcoholic rats.
Keywords: Oxidative stress; Alcohol addiction; Hippocampus; NMDA receptor; Brain; Acamprosate